Handbook of research on Learning design and learning objects issues, applications, and technologies - Lockyer, Lori; Bennett, Sue; Agostinho, Shirley; Harper, Barry (Information Science Reference, 2009)
"This book provides an overview of current research and development activity in the area of learning designs" - Provided by publisher
Includes bibliographical references and index
Keywords: Lernumwelt; Lehr-Lern-Forschung; Aufsatzsammlung